UPM Student goes to bar council - The Sun, S. Tamarai Chelvi (2007)
A Universiti Putra Malaysia (UPM) first-year student, whose hand phone, laptop and other personal item were seized by university security officials, has bought his grouses to the bar council's human rights committee.